The Applied Strategic Planning for the Jordan Football Association from the Perspective of the Professional Clubs' Boards of Directors (for the 2020/2021 season) - ياسين علي المحارمة (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: This study aims to identify the applied strategic planning of the Jordan Football Association from the perspective of the boards of directors of professional clubs for the season 2020/2021, considering their educational qualifications and experience. Methods: The researcher used the descriptive survey method. The study sample consisted of 88 members of the boards of directors committee. The data collection was based on four basic dimensions: commitment to strategic planning, the spread of the strategic planning role, clarity of the concept of strategic planning, and availability of good standards in the components and elements of the strategic plan. Results: Based on the variables of educational qualification and experience, it was found that there was a significant correlation between holding a postgraduate degree and having more experience. Conclusions: The study emphasizes the importance for members of the Jordan Football Association to increase their awareness and enhance the efficiency of proper strategic planning processes before the launch of the sports season each year.